2009
DOI: 10.1302/0301-620x.91b3.20935
|View full text |Cite
|
Sign up to set email alerts
|

Ankle fusion for bone loss around the ankle joint using the Ilizarov technique

Abstract: We present the results of ankle fusion using the Ilizarov technique for bone loss around the ankle in 20 patients. All except one had sustained post-traumatic bone loss. Infection was present in 17. The mean age was 33.1 years (7 to 71). The mean size of the defect was 3.98 cm (1.5 to 12) and associated limb shortening before the index procedure varied from 1 cm to 5 cm. The mean time in the external fixator was 335 days (42 to 870). Tibiotalar fusion was performed in 19 patients and tibiocalcaneal fusion in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…The extended time required for fusion and the fusion rate in their series were similar to those in our complex fusion cohort. In another study, a cohort of patients with posttraumatic bone loss and infection was treated with the Ilizarov method with good results [23]. In that series, 19 of 20 (95%) patients achieved successful fusion after an average of 11 months wearing the external fixator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extended time required for fusion and the fusion rate in their series were similar to those in our complex fusion cohort. In another study, a cohort of patients with posttraumatic bone loss and infection was treated with the Ilizarov method with good results [23]. In that series, 19 of 20 (95%) patients achieved successful fusion after an average of 11 months wearing the external fixator.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle fusion using circular fixation has been regarded as a last resort, limb-salvage procedure [3,5,6,8,10,11,14,16,17,20,21,23,25,[28][29][30][31] (Table 5). We asked whether (1) smoking and other comorbidities (Charcot neuroarthropathy, Type B hosts), (2) time wearing the frame, or (3) tibial lengthening affected union rate after ankle arthrodesis surgery?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Tibiocalcaneal fusion appears to produce favourable functional results, but at the expense of shortening. Dennison et al 10 and Kovoor et al 11 reported tibiotalar or tibiocalcaneal fusion for patients with bone loss of the talus combined with callotasis using the Ilizarov technique, which makes these operations technically demanding. Recently ankle or tibiocalcaneal fusion using allograft has been reported for patients with collapse of the talus and either osteonecrosis or severe bone loss.…”
mentioning
confidence: 99%